INSECTICIDAL AND ANTIOXIDANT ACTIVITIES OF AQUEOUS EXTRACTS OF TWO ALGERIAN MEDICINAL PLANTS (Acta Entomologica Serbica, 2020)
In this work, we determined the insecticidal activity and antioxidant activity of aqueous extracts of Nerium oleander (Apocynaceae) leaves and Peganum harmala (Zygophyllaceae) seeds, two well-known Algerian medicinal plants. Four concentrations of each extract were applied in total randomization by spraying directly on the eggs and larvae of Ectomyelois ceratoniae (Zeller, 1879) (Lepidoptera: Pyralidae) under laboratory conditions. Our findings revealed that eggs hatching after four days were not affected by the aqueous extract, with a rate of 54% of hatching eggs in both control and treated eggs. Additionally, toxicity by contact on larvae was not evident and the mortality percentage did not exceed 8%, regardless of the extract plant and concentration. Phytochemical screening showed a slight presence of terpenes and saponins and an absence of alkaloids. However, polyphenols were present in medium concentrations in the aqueous extracts of both plants. The antioxidant activities of N. oleander and P. harmala extracts were found to be 71.80 and 72.94%, respectively. Total phenolic content (TPC) and total flavonoid content (TFC) of the studied extracts were 50.69 mg gallic acid equivalent (GAE)/100 g dry weight (DW) and 3.55 in terms of quercetin equivalent (QE)/100 g DW, respectively, in N. oleander. In P. harmala, the TPC and TFC were 52.30 mg GAE/100 g DW and 3.49 mg QE/100 g DW, respectively. Our study clearly shows the limited insecticidal effect of the aqueous extracts, although they showed an interesting antioxidant potential, which could help to decrease the incidence of oxidative stress-induced damage.